2018
DOI: 10.2106/jbjs.17.01397
|View full text |Cite
|
Sign up to set email alerts
|

Robotic Technology in Orthopaedic Surgery

Abstract: * Robotic technology used in orthopaedics can be classified on the basis of direct and indirect action and according to the mechanism of cutting, including autonomous, haptic, and boundary control.* Robotics have been used in multiple orthopaedic subspecialties including spine, total joint arthroplasty, trauma, shoulder, and foot and ankle.* Advantages of using robotic technology in orthopaedics include the possibility of improving implant placement (e.g., reducing outliers), accessing certain anatomic areas, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
57
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(58 citation statements)
references
References 83 publications
1
57
0
Order By: Relevance
“…Robot-assisted spinal surgery has been a popular and reliable surgical technique for recent years. 1,7,12,[17][18][19][20][21][22][23][24] Roser et al 24 reported that the accuracy of pedicle screw placement in SpineAssist robot-assisted spinal surgery was 99%. Lonjon et al 25 claimed that the accuracy of pedicle screw placement using the ROSA robot system was 97.3%, compared with 92% using freehand method.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Robot-assisted spinal surgery has been a popular and reliable surgical technique for recent years. 1,7,12,[17][18][19][20][21][22][23][24] Roser et al 24 reported that the accuracy of pedicle screw placement in SpineAssist robot-assisted spinal surgery was 99%. Lonjon et al 25 claimed that the accuracy of pedicle screw placement using the ROSA robot system was 97.3%, compared with 92% using freehand method.…”
Section: Discussionmentioning
confidence: 99%
“…It increases the accuracy and process repeatability of implant placement and has a great potential in making a better and safer clinical outcome for orthopedic operation. 1 With a booming of the technology revolution, operational techniques and implants in spinal surgery continue to develop through these years. 2 In spinal fusion surgery, the accuracy of pedicle screw fixation can be increased significantly with the application of computer-assisted robotic system.…”
Section: Introductionmentioning
confidence: 99%
“…Computer-assisted navigation systems use referencing methods to virtually reconstruct the area of interest and display it on a screen enabling the surgeon to receive real-time feedback intraoperatively [2]. Robotics use computer-guided mechanical arms that enable surgeons to perform surgery remotely, and allow for more accurate and reproducible placement of surgical instruments and implants [3]. Based on the method used for information referencing, navigation systems can be computer tomography (CT)-based, fluoroscopy-based and imageless.…”
Section: The Evolutionmentioning
confidence: 99%
“…Robots can act directly, when they cut the bone to the final desired shape; or indirectly, when they machine features in the bone to allow placement of cutting jigs. Furthermore, robotic bone cutting can be autonomous, when the robot cuts bone with no controlling human hand; haptic, when human interaction is required to move the robot to cut but the robot's movement is constrained by a border; and boundary, when human interaction is required to move the robot but cutting is deactivated or prevented by some means if it travels beyond a boundary even though it is free to move anywhere in space [3].…”
Section: The Evolutionmentioning
confidence: 99%
See 1 more Smart Citation